Smart city technologies from the perspective of technology acceptance. Issue 3 (25th August 2022) - Dirsehan, Taşkın; van Zoonen, Liesbet
Abstract: Most studies in the literature aim to discuss and examine the technologies in smart cities. Much less is known about the dynamics of their acceptance by citizens. Therefore, we conducted a systematic literature review of studies examining the acceptance of smart city technologies (SCTs), focussing particularly on Technology User Acceptance Models (TAM). Using a novel framework of SCTs based on the technology visibility and citizen interaction, we categorise them as individual‐based explicit SCTs, collective‐purpose explicit SCTs, digitising SCTs, and infrastructure SCTs. We assess that studies about citizen acceptation of SCTs have been mainly focussed on individual technologies. Also, the review shows that the field is nascent and fragmented, and that a wide variety of variables have been used to predict the adoption of individual‐based explicit SCTs, with the classic ones of TAM (perceived use and perceived usefulness) unmistakably being relevant in the smart city context as well. As a result of the fragmentation of the field, our review was not yet able to identify generalisable knowledge about the acceptance of the smart city and its technologies by citizens. We end with some suggestions for future research approaches and designs.